EXPERIMENTAL INVESTIGATION OF WAX FORMATION AND ITS MITIGATION IN A MALAYSIAN WAXY CRUDE OIL - ABU, ZULIANA (2013)
The aims for this research study are to identify the wax formation mechanisms involve in the deposition process and analyze the wax crystallization kinetics in agreement to the Avrami theory. The main objectives for this research study are to investigate the effects of varying crude oil temperatures and coolant temperature in absence and presence ofinhibitor, to study the effect of different alkyl chain length of inhibitors, and to study the effect of different concentrations of inhibitors on the wax deposition. Cold finger that represents the process of wax deposition within an oil pipeline was utilizerl Pnlang crude oil from Malaysian offshore was used throughout this study. Pour point depressant (PPD) of different length of alkyl chain was supplied by Petronas Research and Scientific Services Sdn.Bhd. The PPDs were synthesized from polyacrylates and denoted as A10, A14 and A16.